Transforming Corrupt Systems: What Have We Learned?. (18th January 2018) - Fritzen, Scott A.; Dobel, J. Patrick
Abstract : The past two decades have witnessed a growing consensus among policy analysts, political elites, and advocates that corruption is a moral evil with significant deleterious consequences for national economies, social development, and human rights; that leaders across all sectors have a responsibility to fight it; and that a set of anticorruption reforms exists that, if implemented with sufficient "political will, " stand a fighting chance of transforming corrupt systems. This consensus is discussed and two areas in which analytical progress across the field has been piecemeal and unsatisfying to date. The first is the relationship between governance context and the design and sequencing of anticorruption measures. The second concerns the nature of "political will" and the dynamics of change and reform sustainability. To address the "causal complexity" inherent in transforming corrupt systems, a more rigorous comparative research is called for into how interventions function differently across diverse governance environments.